(untitled) (International Journal of Engineering and Computer Science, 2024)
In fiber communication system, delay elements are essential for coherent receivers and in the situation of time division multiplexing. Optical communication is transmitted with light. It has a propagation delay. So, in this system, the performance of optical delay element is demonstrated on wavelength conversion, effects of single mode fiber (SMF) dispersion and fiber length. A numerical simulation is used to predict the performance of delay element for different experimental conditions. It has been proven that when the wavelength is changed and its element covers the entire C band. The system is used with the suitable optical pump power and various fiber lengths. It is accomplished with the various parameters by using Opti-system Software. The system operates near 1550 nm and generates delays time approximately 2.65 nanoseconds. In this paper, the performance value is also stated the table which is comparison of theorical result and practical result of delay time.